1998
DOI: 10.1177/01461672982410001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Attachment to the Group: Cross-Cultural Differences in Organizational Identification and Subjective Norms as Predictors of Workers' Turnover Intentions

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
263
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(296 citation statements)
references
References 42 publications
19
263
0
6
Order By: Relevance
“…There is a special psychological bond between employees and the organization, which determines their work and organizational behaviour. This psychological bond may be expressed by the commitment the employee feels toward the organization (Abrams, Ando, & Hinkle, 1998;Allen & Meyer, 1990;O'Reilly & Chatman, 1986). Research suggests organizational commitment is one of the main predictors of such extra-role behaviour.…”
Section: Note Thatmentioning
confidence: 99%
“…There is a special psychological bond between employees and the organization, which determines their work and organizational behaviour. This psychological bond may be expressed by the commitment the employee feels toward the organization (Abrams, Ando, & Hinkle, 1998;Allen & Meyer, 1990;O'Reilly & Chatman, 1986). Research suggests organizational commitment is one of the main predictors of such extra-role behaviour.…”
Section: Note Thatmentioning
confidence: 99%
“…Ando et al reported that the Japanese subjective norm, which is a psychological element that considers what close people such as family members think, had a greater influence on Japanese in performing PEBs than it did for Germans. Other studies showed that Japanese people cared about other's points of view as part of their culture, and the effect of such attitude on their behaviors was larger than in other cultures [16,23,24]. Aoyagi-Usui et al also concluded in their report that the structure of environmental values and factors encouraging environmental actions differ by country and type of actions [17].…”
Section: Socio-demographics Effects and Psychological Elements Of Envmentioning
confidence: 99%
“…Although people may intend to practice PEBs, various factors such as traditional values, lifestyle, and surrounding circumstances can influence their behavior. In the field of PEB studies, to understand the PEBs deeply, various cross-national studies have been conducted [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%